The solid tumor microenvironment and related targeting strategies: a concise review - Wang, Yingliang; Zhou, Huimin; Ju, Shuguang; Dong, Xiangjun; Zheng, Chuansheng (Frontiers in Immunology, 2025)
The malignant tumor is a serious disease threatening human life. Increasing studies have confirmed that the tumor microenvironment (TME) is composed of a variety of complex components that precisely regulate the interaction of tumor cells with other components, allowing tumor cells to continue to proliferate, resist apoptosis, evade immune surveillance and clearance, and metastasis. However, the characteristics of each component and their interrelationships remain to be deeply understood. To target TME, it is necessary to deeply understand the role of various components of TME in tumor growth and search for potential therapeutic targets. Herein, we innovatively classify the TME into physical microenvironment (such as oxygen, pH, etc.), mechanical microenvironment (such as extracellular matrix, blood vessels, etc.), metabolic microenvironment (such as glucose, lipids, etc.), inflammatory microenvironment and immune microenvironment. We introduce a concise but comprehensive classification of the TME; depict the characteristics of each component in TME; summarize the existing methods for detecting each component in TME; highlight the current strategies and potential therapeutic targets for TME; discuss current challenges in presenting TME and its clinical applications; and provide our prospect on the future research direction and clinical benefits of TME.